Rural household welfare in Papua New Guinea: Food security and nutrition challenges - Schmidt, Emily; Fang, Peixun; Mahrt, Kristi (International Food Policy Research Institute, 2022)
Papua New Guinea continues to encourage a policy focus on food and nutrition security. The PNG National Nutrition Policy (2016-2026) and Nutrition Strategic Action Plan (2018-2022) (NSAP) set a path to improve coordination, secure sufficient funding, and improve technical capacity of nutrition-focused pro gram implementation. As policy prioritizes improved nutrition outcomes, it is important to understand the cost that households face of securing a higher level of nutrition. Ensuring a healthy diet that meets nutrition standards is relatively expensive in PNG. The analysis presented in this paper, which uses detailed household food and non-food consumption data suggests that 4/5 of households in the survey sample live below the healthy diet poverty line (which sets a calorie threshold and defines healthy diet nutrition targets). That is, these households do not have the income available (or do not consume sufficient food and non-food goods) to meet their basic needs which includes securing a nutritious diet that meets food based die tary guidelines.